ʻAnus̨ōn nai ngān phrarātchathān phl̄œng sop Phra Phutthaw̨ōrayān, ʻadīt čhaoʻāwāt Wat Kawitsarārāmmarātchaw̨ōrawihān, Čhao Khana Čhangwat Lop Burī, Mēsāyon Ph̨ō. S̨ō. 2536 - Phra Phutthaw̨ōrayān (Kitti), 1905-1992 (Khana Sit, 1991)
Cremation volume for author, former abbot of Wat Kawitsarārāmmarātchaw̨ōrawihān, Buddhist temple in Lop Buri Province, Thailand; comprises collection of his articles and discourses chiefly on Buddhist doctrines; includes brief biography.